Direct restorative treatment of dental erosion caused by gastroesophageal reflux disease associated with bruxism: a case report - Vidal, Cristina de Mattos Pimenta [UNESP]; Catelan, Anderson [UNESP]; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (AEGIS Communications, 2011)
Gastroesophageal reflux disease (GERD) is a gastrointestinal disorder in which stomach acids are chronically regurgitated into the esophagus and oral cavity. Continual exposure of the teeth to these acids can cause severe tooth wear. Dentists are often the first healthcare professionals to diagnose dental erosion in patients with GERD. This article presents a case report of a 27-year-old male smoker with tooth wear and dentin sensitivity caused by GERD associated with bruxism. After diagnosis, a multidisciplinary treatment plan was established. The initial treatment approach consisted of medical follow-up with counseling on dietary and smoking habits, as well as management of the gastric disorders with medication. GERD management and the dental treatment performed for the eroded dentition are described, including diagnosis, treatment planning, and restorative therapy.